Comparison of dimensional accuracies of stereolithography and powder binder printing. Issue 9 (February 2017) - Islam, M.N.; Gomer, Hayden; Sacks, Samuel
Abstract This paper presents a comparative experimental investigation of the dimensional accuracies of two widely used rapid prototyping (RP) processes: stereolithography (SLA) and powder binder printing (PBP). Four replicates of a purpose-designed component using each RP process were fabricated, and the measurements of the internal and external features of all surfaces were performed using a general-purpose coordinate measurement machine. The results showed that in both cases, the main cause of dimensional variations was the volumetric change inherent in the process. The precision of SLA was far better than that of PBP. The dimensional accuracy of SLA was better in the z direction, whereas PBP produced better dimensional accuracy in thex –y plane. In both RP processes, the height error consisted of two components: constant error and cumulative error. The constant error component was equal to the datum surface error. SLA yielded an average datum surface error that was 68 % higher than in PBP. The height error of SLA improved with the increase in nominal height, whereas it deteriorated in PBP.